Tomas del Rosario College Library an evaluation with implication on the improvement of information resources and of library services - Montanez, Fatima R. (2005)
For the college library to carry out its function effectively, it has to have well-selected information resources, have adequate funding and efficient supervision and administration by a qualified librarian. This research study is intended to determine the strengths and weaknesses of the Tomas del Rosario College Library's collection and services guided by the Philippine Association of Colleges and Universities Commission on Accreditation (PACUCOA) standards.